2019
DOI: 10.1039/c8ra10219h
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of native defects and photoconductivity in ZnO under pressure

Abstract: Control and design of native defects in semiconductors are extremely important for industrial applications.Here, we investigated the effect of external hydrostatic pressure on the redistribution of native defects and their impact on structural phase transitions and photoconductivity in ZnO. We investigated morphologically distinct rod-(ZnO-R) and flower-like (ZnO-F) ZnO microstructures where the latter contains several native defects namely, oxygen vacancies, zinc interstitials and oxygen interstitials. Synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…24,33 In this context, the impacts of various microstructural features, for instance, the distinct shape or morphology, dimension, and homogeneity, of the materials are often found to coincide with the size effects of the nanocrystals in many studies. 9,14,33,3639 The microstructure-induced strains appearing at the contact points of the grains of the materials may cause significant structural distortions, which also contribute to the transition pressure and phase stability. 8,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,33 In this context, the impacts of various microstructural features, for instance, the distinct shape or morphology, dimension, and homogeneity, of the materials are often found to coincide with the size effects of the nanocrystals in many studies. 9,14,33,3639 The microstructure-induced strains appearing at the contact points of the grains of the materials may cause significant structural distortions, which also contribute to the transition pressure and phase stability. 8,14…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, semiconducting nanomaterials of different types and structures have greatly contributed to significant progress in nanoscience and technology due to their salient and flexible opto-electronic, photonic, magnetic, and mechanical features. As far as the exploration of semiconducting nanomaterials under high pressure is concerned, studies on a variety of materials, namely, the group (IV) elements C, Si, and their compound SiC; group (II–VI) compounds such as ZnS, ZnSe, CdS, CdSe, and CdTe; group (IV–VI) PbS; group (III–V) GaN and AlN; the superhard material, BC 2 N; binary oxides such as TiO 2 , ZnO, SnO 2 , Fe 2 O 3 , and CeO 2 ; the rare-earth oxide, Ho 2 O 3 ; wide band-gap oxides such as β-Ga 2 O 3 and Y 2 O 3 ; p-type compounds including CuO, CoO, and MnS; n-type BaTiO 3 ; and narrow band-gap layered group (V–VI) semiconductors such as Bi 2 Te 3 , have been performed. ,,,, Most of these studies have shed light on the interesting kinetics of pressure-induced first-order, solid–solid structural transformations, compressibilities, bulk moduli, and stiffness or hardness of the materials. The thermodynamics of phase transformations and relative stabilities of the phases have also been noted in several studies. ,− Although there are conflicting trends in the reported transition pressures relating to the Hall–Petch effect that is found as bulk materials are reduced to smaller crystallites, a significant influence from nanosized particles or grains has been commonly suggested as the cause for the dissimilar types of nucleation, growth dynamics, phase transition pathways, and even sequences of the phase transitions or amorphizations of semiconducting materials under high pressure. ,,, A specific size, at which the typical nanoscale effects start to occur in materials, has also been defined as their respective “critical size” in several cases. ,, The contributions of the nanoscale-induced differences in the surface energies of the relevant phases mainly account for the stabilities of the corresponding structures. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, such an effect caused by hydrostatic pressure was observed in ZnO microstructures. [22] The Zn accumulation on the hexagonal grain boundaries is in accordance with the decrease of the intensity of the green PL band in ZnO ceramics sintered from the milled powder, which is explained by the decrease of Zn i interstitials.…”
Section: Discussionmentioning
confidence: 52%
“…In a report, Petrera et al observed the spin− lattice relaxation in FeSbO 4 with particle size of ∼250 to 650 Å after calcining a sample with particle sizes of 50 Å above 700 °C. 18 In our study, the observed pressure-induced reduction of crystallite size from ∼58 to ∼53 nm and the associated microscopic strain derived from the Williamson−Hall plot analysis 37 shown in Figure S8b might affect this irreversible phase transition. However, essentially, the lattice distortion at moderate pressures turns semiconducting FeSbO 4 into a highly insulating phase.…”
Section: ■ Results and Discussionmentioning
confidence: 67%